Acute on chronic back pain as the presentation of an occult foreign body bowel perforation with resultant epidural abscess, osteomyelitis and sepsis. Issue 1 (12th January 2021) - Guthrie, Jeff A; Fazio, Michael; Anderson, Todd; Carroll, Christine
Abstract : A 29-year-old male paratrooper presented to multiple emergency departments (EDs) and his primary provider multiple times over sequential days. Each time, the patient received the same diagnosis of acute on chronic back pain. The patient was treated conservatively and routine MRI of the lumbar spine was performed 5 days after the last visit. It revealed a lesion occupying nearly all the visualised portion of the spinal canal. The patient was immediately called back for further imaging. The patient was then diagnosed with a foreign body perforating the rectosigmoid colon, an epidural abscess and pelvic osteomyelitis. The patient was immediately taken to the ED where he was found to be septic. The foreign body was surgically removed and determined to be a swallowed toothpick. Urgent surgical decompression of epidural space was also performed. The patient then underwent a prolonged but near complete recovery.